Teaching Race at Historically White Colleges and Universities: Identifying and Dismantling the Walls of Whiteness. (September 2013) - Brunsma, David L.; Brown, Eric S.; Placier, Peggy
In this article we outline the 'walls of whiteness' that make it difficult to teach the sociology of race and racism and make it difficult for students at historically white colleges and universities (HCWUs) to wrestle with these important issues. Most white students enter HWCUs surrounded by these walls – protecting them from attacks on white supremacy – that have multiple layers and therefore are even more difficult to penetrate; yet they must be penetrated. With a few exceptions, the institution of American higher education does not threaten those walls. Instead, college education often bolsters them through curricular and extracurricular experiences, residential and disciplinary isolation, institutional symbols, cultural reproduction, and everyday practices such as grading and classroom interactions. We identify these walls in this article and make suggestions regarding strategies to begin their dismantling.